IN VITRO CYTOTOXICITY ACTIVITY OF HYDROALCOHOLIC EXTRACT OF POLYHERBAL CHURNAM (COFRI) IN NORMAL LIVER AND KIDNEY CELL LINES - Y, YASMINE; JEBA R, CAROLINE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to investigate the cytotoxic activity of hydroalcoholic extract of a polyherbal powder on Vero (normal kidney) and Chang (normal liver) cell lines. Methods: The cytotoxic effect was evaluated by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-tetrazolium bromide assay. It is commonly used colorimetric assay for assessing cell metabolic activity under specific conditions, indicates the number of viable cells. Results: According to the experimental results, the hydroalcoholic extract does not cause any toxicity on normal liver and kidney cell lines and LC50 values are ca lculated using LDP line software and found 776.73 μg/ml and 686.58 μg/ml. Conclusion: The hydroalcoholic extract of polyherbal churnam exhibited cell viability at higher concentrations. The results indicates investigated formulation does not causes any toxicity to the normal liver and kidney cells and found to be safe for human consumption. Further, toxicological and pharmacological evaluation is required to prove its safety and efficacy.